Peutz–Jeghers syndrome with polyps in the stomach, duodenum, and small and large intestine: a case report - Zaryab Ali Shah; Muhammad Zeb; Muhammad Ilyas; Hasnain Hamid; Komal Fatima; Maria Batool; Muhammad Abbas (Journal of Medical Case Reports, 2024)
Abstract Background Peutz–Jeghers syndrome is a rare hereditary condition characterized by gastrointestinal polyps and pigmented oral lesions. The case contributes to a deeper understanding of Peutz–Jeghers syndrome and underscores the significance of interdisciplinary collaboration for accurate diagnosis and tailored therapeutic strategies. Case description We present a case of a 15-year-old Afghan female patient with multiple polyps throughout the gastrointestinal tract and mucocutaneous pigmentation. Despite previous medical visits and colonoscopies, her symptoms persisted. A multidisciplinary team discussed the case and recommended further investigations and interventions. A polypectomy was performed, confirming the presence of hamartomatous polyps. The patient was diagnosed with Peutz–Jeghers syndrome, but during the course of treatment she went through complications and was managed surgically as well. Conclusion Timely polyp removal and lifelong surveillance are crucial in managing Peutz–Jeghers syndrome. Further research and genetic analysis are needed to improve understanding and management of this rare disorder.